The Moral Meets the Marvellous: Grimms’ Didactic Fairy Tales - Kujundžić Nada (European Society for the Study of English (ESSE), 2025)
The paper proposes to examine the notion of didacticism in Jacob and Wilhelm Grimm’s Kinder- und Hausmärchen (Children’s and household tales, 1812/15–1857), more specifically didactic fairy tales. The broad discussion of some general issues regarding didactic literature is followed by a study of fairy tales containing superimposed didactic insertions and those in which the didactic agenda is supported by the story structure and content. Fairy tales belonging to ATU 480. The Kind and the Unkind Girls have been selected as an illustration of the latter.